Morphological Diversity and Phenetic Relationships among Araceae Species in Lauru I Afulu Village, Indonesia - Nofamataro Zebua; Ite Morina Yostianti Tnunay (GEN BIONIX: Jurnal Ilmiah Pendidikan Biologi, 2026)
Many rural communities have utilized Araceae plants for food, medicine, and ornamental purposes, yet scientific documentation of their diversity and relationships remains limited. This study aimed to analyze the morphological diversity and phenetic relationships among Araceae species in Lauru I Afulu Village, Indonesia. The research was conducted using a descriptive qualitative approach through field observations, interviews, and documentation, with species identified based on morphological characteristics. Data were analyzed using data reduction, classification, and comparative interpretation of morphological traits. The results showed that several genera of Araceae were identified, including Alocasia, Colocasia, Homalomena, Caladium, Aglaonema, and Schismatoglottis, exhibiting distinct variations in leaf shape, stem structure, and tuber characteristics. Species within the same genus demonstrated higher morphological similarity, indicating closer phenetic relationships, while intergeneric differences were more pronounced. A significant finding revealed a strong association between morphological traits and local utilization patterns. These findings highlight the importance of morphological analysis in understanding plant diversity and emphasize the value of integrating local knowledge with scientific approaches for biodiversity documentation and sustainable utilization.